TGF-β/Smad Signaling Pathway in Tubulointerstitial Fibrosis - Yu, Xiao-Yong; Sun, Qian; Zhang, Ya-Mei; Zou, Liang; Zhao, Ying-Yong (Frontiers in Pharmacology, 2022)
Chronic kidney disease (CKD) was a major public health problem worldwide. Renal fibrosis, especially tubulointerstitial fibrosis, is final manifestation of CKD. Many studies have demonstrated that TGF-β/Smad signaling pathway plays a crucial role in renal fibrosis. Therefore, targeted inhibition of TGF-β/Smad signaling pathway can be used as a potential therapeutic measure for tubulointerstitial fibrosis. At present, a variety of targeting TGF-β1 and its downstream Smad proteins have attracted attention. Natural products used as potential therapeutic strategies for tubulointerstitial fibrosis have the characteristics of acting on multiple targets by multiple components and few side effects. With the continuous research and technique development, more and more molecular mechanisms of natural products have been revealed, and there are many natural products that inhibited tubulointerstitial fibrosis via TGF-β/Smad signaling pathway. This review summarized the role of TGF-β/Smad signaling pathway in tubulointerstitial fibrosis and natural products against tubulointerstitial fibrosis by targeting TGF-β/Smad signaling pathway. Additionally, many challenges and opportunities are presented for inhibiting renal fibrosis in the future.